Zirconium oxide composite carrier for vacuum evaporation and preparation method thereof

By adding carbon powder and high-temperature resistant binder to zirconia tablets, high-temperature sintering and low-temperature poremaking processes are adopted, the low porosity and cracking problems of zirconia tablet materials are solved, and vacuum evaporation is improved The specific surface area and stability of the carrier achieve uniformity and wear resistance of the coating, reducing the cost of evaporation.

CN119161205BActive Publication Date: 2025-01-17HUNAN TIANFU NEW MATERIAL CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411673387.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-21
Publication Date
2025-01-17
Estimated Expiration
2044-11-21

Smart Images

  • Figure CN119161205B_ABST
    Figure CN119161205B_ABST
Patent Text Reader

Abstract

The present invention discloses a zirconium oxide composite carrier for vacuum evaporation and a preparation method thereof. The carrier is obtained by sintering the raw material components including the following mass parts: 10-30 parts of zirconium oxide, 1-7 parts of carbon powder, 0.05-6 parts of pore former, and 1-9 parts of high temperature resistant binder; the specific surface area of ​​the composite carrier is 280-310 m 2 / g. The preparation method of the carrier is as follows: mechanically activate zirconium oxide and carbon powder and then perform high-temperature sintering to obtain carbon-zirconium oxide composite particles; the carbon-zirconium oxide composite particles, pore-forming agent and high-temperature resistant binder are evenly mixed and molded to obtain a composite carrier precursor, and then the composite carrier precursor is subjected to low-temperature microwave pore-forming, cleaning and drying in sequence. The composite carrier greatly improves the specific surface area and porosity of the carrier while ensuring the excellent chemical stability of the carrier by strictly limiting the ratio between the raw material components, solves the problems of steel wool carrier being easy to rust and deteriorate, and coating agent being easy to remain, and realizes the reuse of the coating carrier.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a zirconium oxide composite carrier, in particular to a zirconium oxide composite carrier for vacuum evaporation and a preparation method thereof, belonging to the technical field of vacuum evaporation coating. Background Art

[0002] Vacuum evaporation coating refers to a deposition technology that uses the heat energy of a film material heating device (called an evaporation source) under vacuum conditions to evaporate a certain substance and deposit it on the surface of the substrate material. Among them, the coating carrier plays a very important role. It is required to be pure and non-deteriorated, not react with the evaporation agent, and have high temperature resistance.

[0003] Zirconia is a metal oxide with chemical stability, high melting point, high resistivity, high refractive index and low thermal expansion coefficient. Therefore, it is usually used to prepare high-temperature resistant insulating materials, carrier materials for metal catalysts, etc., and has the potential to be used as a coating carrier material. However, the tablet material made by pressing and sintering zirconia has defects such as low porosity, low specific surface area and easy cracking, which limits its further application. Therefore, how to solve the above problems has become the key to preparing new zirconia coating carriers. Summary of the invention

[0004] In view of the problems existing in the prior art, the first object of the present invention is to provide a zirconium oxide composite carrier for vacuum evaporation. The carrier strictly limits the ratio between the raw material components and utilizes the synergistic effect therebetween, thereby greatly improving the specific surface area and porosity of the carrier while ensuring that the carrier has excellent physical and chemical stability, ensuring that the carrier does not react with the coating agent, and further, based on the excellent stability of the carrier, it can effectively solve the problems of steel wool carriers being prone to rust and deterioration, and coating agents being prone to residue in the prior art, thereby realizing the reuse of the coating carrier and greatly saving the evaporation cost.

[0005] The second object of the present invention is to provide a method for preparing a zirconia composite carrier for vacuum evaporation. The method adopts a preparation process of high-temperature calcination-compression molding-low-temperature pore formation, which effectively reduces the interfacial stress between the components of the carrier and greatly improves the bonding force between zirconium oxide and carbon powder; and the low-temperature pore formation process can ensure the uniformity and richness of the internal pore structure of the carrier on the one hand, and can also effectively improve the surface quality of the carrier and avoid cracking and pulverization of the carrier on the other hand.

[0006] In order to achieve the above technical purpose, the present invention provides a zirconium oxide composite carrier for vacuum evaporation, which is obtained by sintering the raw material components including the following mass parts: 10-30 parts of zirconium oxide, 1-7 parts of carbon powder, 0.05-6 parts of pore former, and 1-9 parts of high temperature resistant binder; the specific surface area of ​​the composite carrier is 280-310m2 / g;

[0007] The preparation process of the composite carrier is as follows: mechanically activating zirconium oxide and carbon powder and then sintering at high temperature to obtain carbon-zirconium oxide composite particles; uniformly mixing the carbon-zirconium oxide composite particles, a pore-forming agent and a high-temperature resistant binder and then subjecting the mixture to molding to obtain a composite carrier precursor; and then subjecting the composite carrier precursor to low-temperature microwave pore-forming, cleaning and drying in sequence to obtain the composite carrier.

[0008] In the carrier provided by the present invention, zirconium oxide provides a basic support skeleton for the carrier, and carbon powder is used to effectively improve the thermal conductivity of the carrier, thereby ensuring the smooth evaporation of the coating agent during the evaporation process; the high-temperature resistant binder can effectively reduce the interface effect between the components of the carrier and improve the bonding force, and can also be partially carbonized during the sintering process, thereby further improving the uniformity of the thermal conductivity of the carrier; in addition, the carbon powder can also cooperate with the pore-forming agent to improve the void structure of the carrier, enrich the void structure of the carrier, and ensure the uniform distribution of the pore structure, thereby ensuring the uniformity and flatness of the coating obtained during the evaporation process, and greatly improving the wear resistance of the coated product.

[0009] As a preferred solution, the composite carrier is sintered from raw material components including the following mass parts: 10-20 parts of zirconium oxide, 1-5 parts of carbon powder, 1-4 parts of pore formers, and 2-6 parts of high temperature resistant binders. Further preferably, the composite carrier is sintered from raw material components including the following mass parts: 15 parts of zirconium oxide, 3 parts of carbon powder, 1.5 parts of pore formers, and 4.2 parts of high temperature resistant binders.

[0010] As a preferred solution, the carbon powder is at least one of activated carbon, graphite, carbon black and carbon nanotubes. More preferably, the carbon powder is activated carbon.

[0011] As a preferred solution, the particle size of the carbon powder is -400 mesh.

[0012] As a preferred solution, the pore-forming agent is at least one of ammonium carbonate, ammonium bicarbonate, starch, urea and methyl methacrylate.

[0013] As a preferred solution, the high temperature resistant adhesive is an aluminosilicate adhesive, an aluminum phosphate-based adhesive, or a magnesium aluminum phosphate-based adhesive.

[0014] As a preferred solution, the pore-forming agent is ammonium bicarbonate.

[0015] As a preferred solution, the high temperature resistant binder is an aluminosilicate binder.

[0016] As a preferred solution, the mechanical activation method is ball milling, and the conditions are: ball-to-material ratio is 5-10:1, rotation speed is 150-200 r / min, and time is 2-5 h.

[0017] As a preferred solution, the high temperature sintering process is: in a protective atmosphere, heating from room temperature to 700-1200°C at 10-20°C / min, sintering at this temperature for 0.5-3h, and then cooling to room temperature with the furnace.

[0018] As a preferred solution, the high temperature sintering process is: in a protective atmosphere, the temperature is raised from room temperature to 800-1000°C at 10-20°C / min, sintered for 1-3 hours, and then cooled to room temperature with the furnace. More preferably, the high temperature sintering process is: in a protective atmosphere, the temperature is raised from room temperature to 900°C at 20°C / min, sintered for 2 hours, and then cooled to room temperature with the furnace.

[0019] As a preferred solution, the molding method is cold pressing, and the conditions are: pressure is 0.1-0.2 MPa, and holding time is 15-25 min.

[0020] As a preferred solution, the low-temperature microwave pore-forming process is: under a protective atmosphere, the temperature is raised from room temperature to 200-500°C at 10-20°C / min, the pore-forming is performed for 0.5-3h, and then the pore is cooled to room temperature with the furnace.

[0021] As a preferred solution, the low-temperature microwave pore-forming process is: in a protective atmosphere, the temperature is raised from room temperature to 200-400°C at a rate of 10-20°C / min, the temperature is kept for 0.5-1.5 hours to form pores, and then the furnace is cooled to room temperature. More preferably, the low-temperature microwave pore-forming process is: in a protective atmosphere, the temperature is raised from room temperature to 300°C at a rate of 10°C / min, the temperature is kept for 1 hour to form pores, and then the furnace is cooled to room temperature.

[0022] As a preferred solution, the protective atmosphere is at least one of nitrogen, argon and helium. More preferably, the protective atmosphere is argon.

[0023] Compared with the prior art, the beneficial technical effects of the technical solution of the present invention are:

[0024] 1) The composite carrier provided by the present invention strictly limits the ratio between the raw material components and utilizes the synergistic effect therebetween, thereby greatly improving the specific surface area and porosity of the carrier while also ensuring that the carrier has excellent physical and chemical stability, ensuring that the carrier does not react with the coating agent. Furthermore, based on the excellent stability of the carrier, it can effectively solve the problems in the prior art such as the steel wool carrier being prone to rust and deterioration, and the coating agent being prone to residue, thereby realizing the reuse of the coating carrier and greatly saving the evaporation cost.

[0025] 2) The preparation method provided by the present invention adopts a preparation process of high-temperature calcination-compression molding-low-temperature pore formation, which effectively reduces the interfacial stress between the components of the carrier and greatly improves the bonding force between zirconium oxide and carbon powder; and the low-temperature pore formation process can ensure the uniformity and richness of the internal pore structure of the carrier on the one hand, and on the other hand, it can also effectively improve the surface quality of the carrier and avoid cracking and pulverization of the carrier. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 This is the SEM image of the zirconium oxide coating carrier prepared in Example 1;

[0027] Figure 2 1 and 2 are the evaporation curves of Example 1 (1′), Comparative Example 1 and Comparative Example 6 during the evaporation operation.

[0028] Figure 3 The BET spectrum of the zirconium oxide coating carrier prepared in Example 1;

[0029] Figure 4 This is the BET spectrum of the coated carrier prepared in Comparative Example 3. DETAILED DESCRIPTION

[0030] The present invention is further described below in conjunction with the embodiments, which can enable those skilled in the art to more fully understand the present invention, but does not limit the present invention in any way.

[0031] Example 1

[0032] This embodiment provides a zirconium oxide composite carrier for vacuum evaporation, and the specific preparation process is as follows:

[0033] 1) Weigh 15 parts of zirconium oxide powder and 3 parts of graphite carbon powder in a ball mill, grind and mix them, and the ball milling conditions are: ball-to-material ratio is 10:1, rotation speed is 200r / min, and time is 4h; then transfer them to a microwave tube furnace, heat at a rate of 20℃ / min, and perform high-temperature sintering treatment at 900℃ for 2h in an argon atmosphere. After cooling, wash and dry, then transfer them to a mortar for grinding and sieving to obtain carbon-zirconia particles.

[0034] 2) Add 1.5 parts of ammonium bicarbonate to the carbon-zirconia particles and mix them well, then drop 4.2 parts of aluminosilicate binder, stir well, and then use a tablet pressing mold to form a composite carrier precursor with a single particle weight of 1.3 g and a slightly protruding surface. The cold pressing conditions are: 0.13 MPa, and the holding time is 20 minutes;

[0035] 3) The composite carrier precursor was transferred to a microwave tube furnace, heated at a rate of 10°C / min, sintered and pore-forming at 300°C for 1 hour in an argon atmosphere, and washed and dried after cooling to obtain a zirconium oxide coated carrier with a specific surface area of ​​308.29 m 2 / g.

[0036] 0.5g of AF anti-fingerprint agent was added to the zirconium oxide coating carrier prepared according to the above preparation steps, and then vacuum evaporation coating was performed. After the coated substrate was left to stand and cleaned and dried, the initial water contact angle test was performed, and the result was recorded as the initial water contact angle; then, the rubber and steel wool were used for friction resistance test respectively. The rubber was rubbed 8k times, and the steel wool was rubbed 5k times. After each 1k times of friction, new steel wool was replaced. After the friction was completed, the water contact angle was recorded again, and this group of data was recorded as 1′.

[0037] After the first evaporation, the carrier is rinsed with distilled water and dried, and then evaporated for the second and third time according to the above execution requirements. The test data of the obtained substrates are recorded as 2' and 3' respectively.

[0038] Example 2

[0039] This embodiment is completely consistent with Embodiment 1, except that:

[0040] 1) Weigh 17 parts of zirconium oxide powder and 4 parts of bamboo charcoal powder in a ball mill, grind and mix them, then transfer them to a microwave tube furnace, heat them at a rate of 20°C / min, and perform high-temperature sintering at 850°C for 2 hours in an argon atmosphere. After cooling, wash and dry, transfer them to a mortar for grinding and sieving to obtain carbon-zirconia particles;

[0041] 2) Add 1 part of starch to the carbon-zirconia particles and mix well, drop 5 parts of aluminosilicate binder, stir well, and then use a tablet pressing mold to form a single particle with a mass of 1.5 g and a slightly protruding surface as a tablet composite carrier precursor;

[0042] The coating carrier obtained in Example 2 was used in the evaporation experiment in the same manner as in Example 1. The initial contact angle of the coating substrate and the contact angle after being rubbed with rubber for 8000 times and with steel wool for 5000 times are shown in Table 1.

[0043] Example 3

[0044] This embodiment is completely consistent with Embodiment 1, except that:

[0045] 1) Weigh 14 parts of zirconium oxide powder and 3 parts of reed straw carbon powder in a ball mill, grind and mix them, then transfer them to a microwave tube furnace, heat them at a rate of 20°C / min, and sinter them at 1000°C for 2 h in an argon atmosphere. After cooling, wash and dry, transfer them to a mortar for grinding and sieving to obtain carbon-zirconium oxide particles.

[0046] 2) Add 1 part of ammonium bicarbonate to the carbon-zirconia particles and mix well, dropwise add 3.5 parts of aluminum phosphate-based binder, stir well, and then pass through a tablet pressing mold to form a composite carrier precursor with a single particle weight of 1.1 g and a slightly protruding surface;

[0047] 3) The composite carrier precursor is transferred to a microwave tube furnace, heated at a rate of 10°C / min, sintered and pore-formed at 400°C for 1 hour in an argon atmosphere, and then cleaned and dried after cooling to obtain a zirconium oxide coated carrier.

[0048] The coating carrier obtained in Example 3 was used in the evaporation experiment in the same manner as in Example 1. The initial contact angle of the coating substrate and the contact angle after being rubbed with rubber for 8000 times and with steel wool for 5000 times are shown in Table 1.

[0049] Example 4

[0050] This embodiment is completely consistent with Embodiment 1, except that:

[0051] 1) Weigh 20 parts of zirconium oxide powder and 5 parts of coconut shell carbon powder in a ball mill, grind and mix them, then transfer them to a microwave tube furnace, heat them at a rate of 15°C / min, and sinter them at 800°C for 2 hours in an argon atmosphere. After cooling, wash and dry them, then transfer them to a mortar for grinding and sieving to obtain carbon-zirconium oxide particles.

[0052] 2) adding 1 part of ammonium bicarbonate to the carbon-zirconia particles and mixing them well, dropping 2.2 parts of aluminosilicate binder, stirring well, and then pressing the mixture into a tablet having a mass of 1.2 g and a slightly protruding surface through a tablet pressing mold;

[0053] The coating carrier obtained in Example 4 was used in the evaporation experiment in the same manner as in Example 1. The initial contact angle of the coating substrate and the contact angle after being rubbed with rubber for 8000 times and with steel wool for 5000 times are shown in Table 1.

[0054] Comparative Example 1

[0055] Compared with Example 1, the difference is that in step S1, no graphite carbon powder is added, but high-temperature sintering is directly performed, and the other preparation steps are the same.

[0056] The coating carrier obtained in Comparative Example 1 was used in the evaporation experiment in the manner of Example 1. The initial contact angle of the coating substrate and the contact angle after being rubbed with rubber for 8000 times and with steel wool for 5000 times are shown in Table 1.

[0057] Comparative Example 2

[0058] Compared with Example 1, the difference is that the high-temperature sintering treatment at 900° C. is changed to 300° C., and the other preparation steps are the same.

[0059] The coating carrier obtained in Comparative Example 2 was used in the evaporation experiment in the manner of Example 1. The initial contact angle of the coating substrate and the contact angle after being rubbed with rubber for 8000 times and steel wool for 5000 times are shown in Table 1.

[0060] Comparative Example 3

[0061] Compared with Example 1, the difference is that ammonium bicarbonate is not added, but the high temperature resistant binder is directly added dropwise. The other preparation steps are the same. The specific surface area of ​​the carrier is 45.36m 2 / g.

[0062] The coating carrier obtained in Comparative Example 3 was used in the evaporation experiment in the same manner as in Example 1. The initial contact angle of the coating substrate and the contact angle after being rubbed with rubber for 8000 times and with steel wool for 5000 times are shown in Table 1.

[0063] Comparative Example 4

[0064] Compared with Example 1, the difference is that no high temperature resistant binder is added, but distilled water is used instead, and the other preparation steps are the same.

[0065] The coating carrier obtained in Comparative Example 4 was used in the evaporation experiment in the same manner as in Example 1. The initial contact angle of the coating substrate and the contact angle after being rubbed with rubber for 8000 times and with steel wool for 5000 times are shown in Table 1.

[0066] Comparative Example 5

[0067] Compared with Example 1, the difference is that the low-temperature 300°C calcination treatment is changed to a high-temperature 1000°C, and the other preparation steps are the same.

[0068] The coating carrier obtained in Comparative Example 5 was used in the evaporation experiment in the same manner as in Example 1. The initial contact angle of the coating substrate and the contact angle after being rubbed with rubber for 8000 times and with steel wool for 5000 times are shown in Table 1.

[0069] Comparative Example 6

[0070] Traditional steel wool was used as a coating carrier for evaporation experiments in the manner of Example 1. The initial contact angle of the coated substrate and the contact angle after being rubbed with rubber for 8000 times and with steel wool for 5000 times are shown in Table 1.

[0071] After the first evaporation, the carrier is rinsed with distilled water and dried, and then evaporated for the second and third time according to the above execution requirements. The test data of the obtained substrates are recorded as 2' and 3' respectively.

[0072] The specific implementation requirements of the abrasion resistance test are as follows: The steel wool abrasion resistance test is measured by a ZJ-339-GSR abrasion resistance tester, the coated substrate is fixed on the tester, the rubber model is MUNBANGSAWOO, the pressure is set to 1000g, the stroke is set to 40mm, and the speed is 40cycles / min.

[0073] Contact angle test method: The static contact angle of the coating is measured by a JGW-360a contact angle meter. The test liquid volume is 2μL, the test environment is 24±1℃, and the relative humidity is 45±1%. The water droplet contact angle is measured at 5 points and the average value is taken.

[0074]

[0075] It can be seen from Table 1 that the composite carrier provided by the present invention is basically the same as the steel wool carrier in terms of coating performance. However, in the repeated evaporation process, the composite carrier provided by the present invention is significantly better than the steel wool carrier and has excellent repeatability, which effectively solves the problems that the steel wool carrier is easy to rust and deteriorate and cannot be reused. Furthermore, the present invention also conducted scanning electron microscopy and BET tests on the composite carrier obtained in Example 1, and the results are as follows: Figure 1 and Figure 3 As shown. Figure 1 and Figure 3 It can be seen that the surface of the composite carrier presents a rich and dense pore structure, and its specific surface area reaches 308.29m 2 / g, relative to the specific surface area of ​​45.36 m2 of the zirconium oxide coating carrier prepared in Comparative Example 3. 2 / g, the addition of pore-forming agent is beneficial to the adhesion of coating agents.

[0076] The above embodiments are only for better explanation of the principles and practical applications of the present invention, so that those skilled in the relevant technical field can better understand and utilize the present invention, but they are not intended to limit the patent scope of the present invention. All equivalent changes made using the contents of the present invention are within the patent protection scope of the present invention.

Claims

1. A zirconium oxide composite carrier for vacuum evaporation, characterized in that: The composite carrier is obtained by sintering the raw material components including the following parts by weight: 10-30 parts of zirconium oxide, 1-7 parts of carbon powder, 0.05-6 parts of pore-forming agent, and 1-9 parts of high-temperature resistant binder; the specific surface area of ​​the composite carrier is 280-310m 2 / g; The preparation process of the composite carrier is as follows: mechanically activating zirconium oxide and carbon powder and then sintering at high temperature to obtain carbon-zirconium oxide composite particles; The carbon-zirconia composite particles, pore-forming agent and high temperature resistant binder are mixed evenly and then molded to obtain a composite carrier precursor, and then the composite carrier precursor is subjected to low temperature microwave pore-forming, cleaning and drying in sequence to obtain; The low-temperature microwave pore-making process is: heating from room temperature to 200-500° C. under a protective atmosphere.

2. A zirconium oxide composite carrier for vacuum evaporation according to claim 1, characterized in that: The carbon powder is at least one of activated carbon, graphite, carbon black and carbon nanotubes; and the particle size of the carbon powder is -400 mesh.

3. The zirconium oxide composite carrier for vacuum evaporation according to claim 1, characterized in that: The pore-forming agent is at least one of ammonium carbonate, ammonium bicarbonate, starch, urea and methyl methacrylate; the high temperature resistant adhesive is an aluminosilicate adhesive, an aluminum phosphate-based adhesive, or a magnesium aluminum phosphate-based adhesive.

4. A zirconium oxide composite carrier for vacuum evaporation according to claim 1 or 3, characterized in that: The pore-forming agent is ammonium bicarbonate; the high-temperature resistant binder is an aluminosilicate binder.

5. The zirconium oxide composite carrier for vacuum evaporation according to claim 1, characterized in that: The mechanical activation method is ball milling, and the conditions are: ball-to-material ratio is 5-10:1, rotation speed is 150-200 r / min, and time is 2-5 hours.

6. The zirconium oxide composite carrier for vacuum evaporation according to claim 1, characterized in that: The high temperature sintering process is: in a protective atmosphere, heating from room temperature to 700-1200° C. at 10-20° C. / min, sintering at this temperature for 0.5-3 hours, and then cooling to room temperature along with the furnace.

7. The zirconium oxide composite carrier for vacuum evaporation according to claim 1, characterized in that: The molding method is cold pressing, and the conditions are: pressure is 0.1-0.2 MPa, and holding time is 15-25 min.

8. The zirconium oxide composite carrier for vacuum evaporation according to claim 1, characterized in that: The heating rate of the low-temperature microwave pore making is 10-20°C / min, and the heat preservation pore making time is 0.5-3h.

9. A zirconium oxide composite carrier for vacuum evaporation according to claim 6 or 8, characterized in that: The protective atmosphere is at least one of nitrogen, argon and helium.

Citation Information

Patent Citations

  • Insulating heat-dissipating nano composite ceramic

    CN108191407A

  • Preparation method of zirconia porous ceramic

    CN108467281A